TINJAUAN ETNOEKOLOGI DAN BEBERAPA PENELITIAN DI INDONESIA (Review of Ethnoecology and Some of Its Studies in Indonesia) - Maikel Simbiak (Universitas Cenderawasih, 2016)
Maikel Simbiak. 2018. Review of Ethnoecology and Some of Its Studies in Indonesia.Â Ethnoecology is an interdisciplinary field that sounds new in the treasury of science but has lasted a long time in practice. Ethnoecology in the results of his studies also showed a variety of colours according to the background of the practitioners. Nevertheless, ethnoecology has made a real contribution in environmental conservation efforts. The concepts and practices of environmental management of traditional community that has played a role in environmental conservation are well documented. Principles of the concept and practice are then implemented in environmental management in this modern era. In this review, the author wishes to give a little explanation about ethnobiology as a science and how this field has found some of the application of knowledge/concept of traditional landscape management in environmental conservation currently.Â Keywords: environmental conservation, ethnoecology, landscape management